E-BOOK WITH A REALISTIC MATHEMATICS EDUCATION APPROACH HELPED BY SMART APPS CREATOR TO IMPROVE STUDENTS' PROBLEM SOLVING ABILITIES - Putri, Puput Diana; Suwanto, Fevi Rahmawati (UNDIKMA, 2025)
The low problem solving ability of students at SMP Negeri 1 Kisaran is influenced by the use of less varied teaching materials. This research aims to produce E-Book products with the Realistic Mathematics Education (RME) approach assisted by Smart Apps Creator to improve students' problem solving skills that meet valid, practical, and effective criteria. This development uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The sample consists of two classes, namely class VIII-5 (experimental) and class VIII-2 (control), each with 30 students. Data were collected through tests, namely pretest posttest and non-test consisting of observation, interview, and questionnaire. Analysis data were analyzed through independent sample t-test with the help of SPSS 25. The results showed that: (1) The developed E-Book meets the valid criteria with an average expert assessment of 87.4% “very valid” category. (2) The practicality of the E-Book is obtained from the results of the teacher and student response questionnaire with an average value of 88.8% “very practical” category. (3) Based on the results of the Independent Samples T-test test, the sig. (2-tailed) 0.000 <0.05, which means there is a significant difference between the experimental class and the control class. Thus, the use of E-Books with the RME approach assisted by Smart Apps Creator is effective in improving students' problem solving skills.